2016
DOI: 10.1093/mnras/stw1923
|View full text |Cite
|
Sign up to set email alerts
|

Stellar activity with LAMOST – I. Spot configuration in Pleiades

Abstract: We use the spectra of Pleiades and field stars from LAMOST DR2 archive to study how spottedness and activity vary as a function of mass at young ages. We obtained standard TiO band strength by measuring TiO bands near 7050Å from LAMOST spectra (R≈1800) for large sample of field GKM dwarfs with solar metallicity. Analysis show that active dwarfs, including late G-and early K-type, have extra TiO absorption compare to inactive counterparts, indicating the presence of cool spots on their surface. Active late K-an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 90 publications
(149 reference statements)
4
48
0
Order By: Relevance
“…Such a turbulent dynamo can naturally explain the weak dependency of activity on rotation among fast rotators in the saturation regime. Moreover, the generation of small-scale magnetic field supports some observational behaviour shown by very active stars, e.g., large spot coverage of stars in young open clusters may be due to many small and randomly located spots on the stellar photosphere , 2013Fang et al 2016), and the possibility of multiple small flares such as nanoflares that might be responsible for the departures of relation between various chromospheric emissions among very active late-K and M dwarfs reported by previous studies and discussed above in current work. We thus conclude that a turbulent-like dynamo dominates in fast rotating cool stars in the saturated regime.…”
Section: What Can We Learn From the Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Such a turbulent dynamo can naturally explain the weak dependency of activity on rotation among fast rotators in the saturation regime. Moreover, the generation of small-scale magnetic field supports some observational behaviour shown by very active stars, e.g., large spot coverage of stars in young open clusters may be due to many small and randomly located spots on the stellar photosphere , 2013Fang et al 2016), and the possibility of multiple small flares such as nanoflares that might be responsible for the departures of relation between various chromospheric emissions among very active late-K and M dwarfs reported by previous studies and discussed above in current work. We thus conclude that a turbulent-like dynamo dominates in fast rotating cool stars in the saturated regime.…”
Section: What Can We Learn From the Resultssupporting
confidence: 65%
“…Wright et al 2011), chromospheric Ca ii and Hα emissions (e.g. Noyes et al 1984;Jackson & Jeffries 2010;Douglas et al 2014;Newton et al 2017), and cool spot coverages (Fang et al 2016). …”
Section: Rotation-activity Correlationmentioning
confidence: 99%
“…Gully-Santiago et al (2017) studied the T-Tauri star LkCa 4 and found that spectra features in high-resolution near-infrared spectra were produced by hot (∼4100 K) and cool photospheric components (∼ 2700-3000 K), with the cool component covering ∼80% of the stellar surface. TiO bands in R∼1, 000 spectra of a large sample of stars in the Pleiades show that spot covering fractions of ∼50% are common among K and M stars at ∼125 Myr (Fang et al 2016).…”
Section: Trappist-1 Results In Contextmentioning
confidence: 99%
“…LAMOST has an ideal view of the field observed for four years by the Kepler satellite, and several groups have used the ∼50,000 stars observed in the Kepler field to characterize its stellar populations (e.g., Dong et al 2014;Frasca et al 2016;Ren et al 2016;Chang et al 2017;Dong et al 2017). Other work based on LAMOST spectra includes measurements of stellar activity (e.g., Fang et al 2016) and identification of important subclasses of objects from ultra-metal-poor stars (e.g., and metalliclined Am stars (e.g., Hou et al 2015).…”
Section: Overview Of the Survey Landscapementioning
confidence: 99%